Primary gestational choriocarcinoma of the uterine cervix. Report of a case and review of the literature. Issue 4 (1st July 2007) - Kairi-Vassilatou, E.; Papakonstantinou, K.; Grapsa, D.; Kondi-Paphiti, A.; Hasiakos, D.
Abstract : Gestational choriocarcinoma usually arises in the uterine cavity and is associated with coincident or antecedent pregnancy. Extrauterine choriocarcinomas are very rare entities, and most of these are located in the uterine cervix. In our case, a 43-year-old woman was admitted in our hospital because she had amenorrhea for 2 months and elevated serum beta-human chorionic gonadotropin levels. The patient was considered to have an ectopic pregnancy. Initially, she was treated with methotrexate, but since there was a continuous rise in human chorionic gonadotropin levels, the patient underwent a laparoscopy, along with dilatation and curettage (D&C) of the uterine cavity. Histopathologic findings, including immunohistochemical study, led to the diagnosis of choriocarcinoma of the cervix. Finally, the patient underwent a transabdominal hysterectomy and received single agent chemotherapy with methotrexate. Our case represents a primary choriocarcinoma of the cervix, which was initially misdiagnosed as an ectopic pregnancy. The difficulties in differential diagnosis are discussed. Immunohistochemical evaluation remains the mainstay of the diagnosis in most cases. Choriocarcinoma has a very good prognosis even in advanced stages, since it is a very chemosensitive tumor